Investigating ethnic differences in sexual health: focus groups with young people. Issue 4 (4th August 2004) - Connell, P; McKevitt, C; Low, N
Abstract : Objectives: To compare normative beliefs about sexual health in young men and women from black Caribbean, black African, and white ethnic groups in order to better understand ethnic inequalities in sexual health. Methods: Focus group discussions with young people living in an area with known high prevalence of gonorrhoea and chlamydia. Groups were stratified by sex and self defined ethnicity. Results: 22 male and 20 female 16–25 year olds of black Caribbean, black African, and white ethnicity took part in eight discussions. Participants from black ethnic groups were more aware of gonorrhoea than white participants but all ethnic groups regarded these as being less important than unplanned pregnancy or HIV/AIDS. Most participants believed that they would have obvious symptoms if they had a sexually transmitted infection and could determine the cleanliness of sexual partners by visual or behavioural cues. Black Caribbean women were alone in acknowledging the likelihood of their partners having concurrent sexual relationships. Some black Caribbean women described negative attitudes of staff in genitourinary medicine clinics who were from the same ethnic background. Conclusion: In this focus group study we identified ethnic differences in terminology, awareness of sexually transmitted infections, non-exclusive sexual relationships, and experience of sexual health services but gender had a greater influence on normative beliefs. The similarities in norms for all ethnic groups might reflect common social and cultural exposures. The low priority given to sexually transmitted infections by young people from all ethnic groups needs to be addressed if they are to be tackled successfully.